THREE-SITE PHOTOMETRIC MONITORING OF THE δ SCT-TYPE PULSATING STAR V1162 ORIONIS : PERIOD CHANGE AND ITS IMPLICATIONS FOR PRE-MAIN SEQUENCE EVOLUTION - KIM, SEUNG-LEE; CHA, SANG-MOK; LIM, BEOMDU; LEE, JAE WOO; LEE, CHUNG-UK; LEE, YONGSEOK; KIM, DONG-JIN; LEE, DONG-JOO; KOO, JAE-RIM; HONG, KYEONGSOO; RYU, YOON-HYUN; PARK, BYEONG-GON (Journal of The Korean Astronomical Society, 2016)
We present photometric results of the $δ$ Sct star V1162 Ori, which is extensively monitored for a total of 49 nights from mid-December 2014 to early-March 2015. The observations are made with three KMTNet (Korea Microlensing Telescope Network) 1.6 m telescopes installed in Chile, South Africa, and Australia. Multiple frequency analysis is applied to the data and resulted in clear detection of seven frequencies without an alias problem\,: five known frequencies and two new ones with small amplitudes of 1.2-1.7 mmag. The amplitudes of all but one frequency are significantly different from previous results, confirming the existence of long-term amplitude changes. We examine the variations in pulsation timings of V1162 Ori for about 30 years by using the times of maximum light obtained from our data and collected from the literatures. The $O-C$ (Observed minus Calculated) timing diagram shows a combination of a downward parabolic variation with a period decreasing rate of (1/P)dP/dt = $-$4.22 $×$ 10$^{-6}$ year$^{-1}$ and a cyclic change with a period of about 2780 days. The most probable explanation for this cyclic variation is the light-travel-time effect caused by an unknown binary companion, which has a minimum mass of 0.69 M$_\odot$. V1162 Ori is the first $δ$ Sct-type pulsating star of which the observed fast period decrease can be interpreted as an evolutionary effect of a pre-main sequence star, considering its membership of the Orion OB 1c association. KCI Citation Count: 0